Twelve Tips for Establishing an Effective Quality Assurance System for Medical Schools - Noushin Kohan; Soleiman Ahmady; Yadolah Zarezadeh; Seyed Ahmad Ahmadi Teymourlouy (Acta Medica Iranica)
Quality standards must be established and continually improved through innovations and regular monitoring in medical educational institutions. In addition, medical education must be supported by a quality culture, as well as quality assurance systems. Assuring quality in medical education institutions is a serious concern for policymakers. A major problem is that the quality assurance system is not fully implemented locally, and the institutes lack a robust and comprehensive quality assurance system that can function effectively. These 12 tips provide guidance to medical schools involved in the installation of quality assurance systems. Using these tips will allow medical schools to ensure their quality assurance system reflects their overall mission and goals.